PENGARUH JENIS PELARUT TERHADAP EKSTRAKSI DARI KULIT BUAH NAGA MERAH (Hylocereus polyrhizus) - Amalia Noviyanty; Chitra Anggriani Salingkat; Syamsiar Syamsiar (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2019)
This study aims to determine the effect of the type of solvent on extract yield, total phenolics and IC50 values of the skin of red dragon fruit and also obtain the best type of solvent that provides extract rendement, total phenolics and the highest or best IC50 value for extracting red dragon fruit peels. There are 3 types of solvents used (95% ethanol, ethyl acetate and acetone: water (7: 3) with a sample-solvent ratio (5:1 v/b). The data obtained were analyzed using a Completely Randomized Design that was applied to observations of extract rendemen, phenolics total and IC50 values, if the treatment had a very significant or significant effect followed by continued BNJ test at 1% or 5% level. The results showed that the solvent ratio very significantly affected the extract rendemen, phenolics total and IC50 value of red dragon fruit peel extract. Ethanol 95% solvent is the best solvent for extracting dragon fruit peels because it has the highest yield (26.15%), total phenolic (64.75 ppm) and antioxidant activity (IC50 value) (120.53 ppm) highest or best. Keywords : IC50, the red dragon fruit skin, solvent ratio, extract yield, phenolics total